Menstrual blood-derived mesenchymal stromal cell extracellular vesicles – a potential tool for tissue regeneration and disease detection - Vaiciuleviciute, Raminta; Pachaleva, Jolita; Bernotiene, Eiva; Kugaudaite, Gabija; Lebedis, Ignas; Krugly, Edvinas; Uzieliene, Ilona (Frontiers in Bioengineering and Biotechnology, 2025)
Menstrual blood-derived mesenchymal stromal cells (MenSCs) have emerged as a novel source for regenerative medicine, offering a unique alternative to traditional stem cell types, including adipose-derived and bone marrow-derived mesenchymal stromal cells. MenSCs are characterized by their pluripotency, multi-lineage differentiation potential and immunomodulatory properties, which enable them to contribute to the regeneration of various tissues such as skin, uterus, muscle, connective tissues and nerves. Extracellular vesicles (EVs) secreted by MenSCs contain biologically active molecules, including proteins, lipids, and miRNAs, which play a key role in mediating these regenerative effects. Compared to other MSC-derived EVs, MenSC-EVs offer distinct advantages due to their enhanced regenerative capabilities and lower immunogenicity. Moreover, MenSC-EVs are a promising source for disease biomarkers in various diseases, including female reproductive system issues such as infertility. This manuscript reviews the latest findings on MenSCs and their EVs, highlighting their cargo composition, regenerative potential and as a source of biomarkers across multiple tissues, comparing their cargo profiles with EVs derived from other MSC sources.